Needs Analysis for the Development of an Inquiry-Based Learning E-Module Integrated with Deep Learning to Facilitate Students’ Creative Thinking Skills on Heat Concepts - Syalsahadi Rivai; Emiliannur Emiliannur; Fatni Mufit; Hayyu Yumna (Department of Physics Universitas Negeri Padang, 2026)
Efforts to develop 21st-century skills are focused on a student-centered learning approach, where educators act as facilitators in supporting the learning process. One of the main focuses in this skill is the development of four core competencies known as the 4Cs: creative thinking, critical thinking, communication, and collaboration skills. One of the four most important skills that students must develop is creative thinking. However, in reality, mastery of this skill remains relatively low. This low ability is caused by teaching materials used in the learning process that have not been fully designed to support students' creative thinking skills and the inquiry-based learning model. This study aims to analyze the needs of e-modules based on an inquiry-based learning model integrated with deep learning. This study used a development research approach with the 4-D model (Define, Design, Development, and Disseminate), which was limited to the Development stage. The results revealed three main findings from the needs analysis: (1) the creative thinking skills of 11th-grade students at SMAN 2 Padang are still classified as very low with an average score of 40%; (2) the teaching materials used are still limited to printed textbooks and are not yet able to optimally facilitate students' creative thinking skills; (3) The results of the analysis of student characteristics show that 92% of students have a positive view of the use of digital teaching materials. Support for these digital learning materials is also seen from the results of the questionnaire which shows that students find it easier to understand Physics material through videos or online simulations and require learning materials equipped with visual elements, multimedia, such as images, animations, and learning videos, with an average percentage of 92%. In addition, the potential for utilizing digital learning materials in the learning process is considered very large, considering that around 91% of students already have smartphones that can be used for digital-based learning. The research conclusion obtained from the needs analysis is that the development of E-Modules based on inquiry-based learning integrated with deep learning to facilitate students' creative thinking skills on heat material is very much needed by students